2020
DOI: 10.1016/j.arcmed.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

S1 Subunit and Host Proteases as Potential Therapeutic Avenues for the Treatment of COVID-19

Abstract: The novel corona virus (SARS-CoV-2) that causes severe acute respiratory syndrome, now called COVID-19 initially originated in Wuhan city of China and later spread across borders and infected more than five million people and killed over 3.4 lakh people all over the globe. This disease has been announced as pandemic by WHO. So far, there has been not much progress in terms of drug development for fighting against this deadliest virus, also no existing drugs has been reported completely effective for COVID-19 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Notes: Reprinted from Archives of Medical Research, Vol 66, Arafah A, Ali S, Yatoo AM, Ali MN, Rehman MU, S1 subunit and host proteases as potential therapeutic avenues for the treatment of COVID-19, In press, Copyright (2020), with permission from Elsevier. 10 COVID-19 and then reported satisfactory clinical results with arbidol and LPV/r compared to LPV/r alone.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Notes: Reprinted from Archives of Medical Research, Vol 66, Arafah A, Ali S, Yatoo AM, Ali MN, Rehman MU, S1 subunit and host proteases as potential therapeutic avenues for the treatment of COVID-19, In press, Copyright (2020), with permission from Elsevier. 10 COVID-19 and then reported satisfactory clinical results with arbidol and LPV/r compared to LPV/r alone.…”
Section: Figurementioning
confidence: 99%
“…Also, some researchers suggested that S1 subunit and host proteases play potential therapeutic roles in the treatment of COVID-19 ( Figure 3). 10 In this regard, it was shown that Zoonotic β-coronaviruses have a high binding affinity towards angiotensin converting enzyme 2(ACE2), which serves as an operative receptor for viral entry to the host cell. ACE2 have also been reported as cellular receptors used by β-coronaviruses MERS-CoV and bat coronavirus.…”
Section: Introductionmentioning
confidence: 99%
“…The virus relies on the spike(S) protein on its envelope surface to mediate recognition and fusion between the virus and the host cell, thus causing infection [12] . The S protein of SARS-CoV-2 can be cleaved into S1 and S2 subunits by the action of host proteases, which are responsible for receptor binding and membrane fusion, respectively [13] , [14] .…”
Section: Sara-cov-2 Hijacked the Host Mitochondriamentioning
confidence: 99%